Usefulness of AFP, AFP-L3, and PIVKA-II, and their combinations in diagnosing hepatocellular carcinoma. Issue 11 (March 2017) - Park, Sang Joon; Jang, Jae Young; Jeong, Soung Won; Cho, Young Kyu; Lee, Sae Hwan; Kim, Sang Gyune; Cha, Sang-Woo; Kim, Young Seok; Cho, Young Deok; Kim, Hong Soo; Kim, Boo Sung; Park, Suyeon; et al.
Abstract : Abstract: Alpha-fetoprotein (AFP), Lens culinaris -agglutinin-reactive fraction of AFP (AFP-L3), and protein induced by vitamin K absence or antagonist-II (PIVKA-II) are widely used as tumor markers for the diagnosis of hepatocellular carcinoma (HCC). This study compared the diagnostic values of AFP, AFP-L3, and PIVKA-II individually and in combination to find the best biomarker or biomarker panel. Seventy-nine patients with newly diagnosed HCC and 77 non-HCC control patients with liver cirrhosis were enrolled. AFP, AFP-L3, and PIVKA-II were measured in the same serum samples using microchip capillary electrophoresis and a liquid-phase binding assay on an automatic analyzer. Receiver-operating characteristic curve analyses were also applied to all combinations of the markers. When the 3 biomarkers were analyzed individually, AFP showed the largest area under the receiver-operating characteristic curve (AUC) (0.751). For combinations of the biomarkers, the AUC was highest (0.765) for "PIVKA-II > 40 mAU/mL and AFP > 10 ng/mL." The combination of "PIVKA-II > 40 mAU/mL and AFP > 10 ng/mL and AFP-L3 > 10%" had worse sensitivity and lower AUC ( P = 0.001). The highest AUC of a single biomarker was highest for AFP and of a combination was "PIVKA-II > 40 mAU/mL and AFP > 10 ng/mL, " with this also being the case when the cut-off value of AFP and AFP-L3 was changed. Alpha-fetoprotein showed the best diagnostic performance as a single biomarker for HCC. The diagnostic value of AFP was improved by combining it with PIVKA-II, but adding AFP-L3 did not contribute to the ability to distinguish between HCC and non-HCC liver cirrhosis. These findings were not altered when the cut-off value of AFP and AFP-L3 was changed. Abstract : Supplemental Digital Content is available in the text